2018
DOI: 10.1155/2018/3012081
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Effect on the Solid-Surface Fluorescence of Pyrene on Cellulose Diacetate Matrices

Abstract: The effect of the solvent nature (acetonitrile, ethanol, dimethyl sulfoxide, and dioxane) and its concentration on the fluorescence intensity of pyrene sorbed on the cellulose diacetate (CDA) film from a water-organic solution was studied. Dimethyl sulfoxide and ethanol are shown to be the most effective solvent additives for pyrene solid-surface fluorescence (SSF). The maximum SSF signal of pyrene was found upon sorption of the substance from aqueous media containing 1.2-4.2 vol% DMSO. For the pyrene quantita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…were determined by luminescence analysis. For example, in the study [31], the PYRE concentration on solid matrices was determined using a calibration graph. The authors found that the dependence of the SPL intensity on the PAHs concentration on the solid matrix is linear up to CPAHs = 2 × 10 -8 g/l.…”
Section: Resultsmentioning
confidence: 99%
“…were determined by luminescence analysis. For example, in the study [31], the PYRE concentration on solid matrices was determined using a calibration graph. The authors found that the dependence of the SPL intensity on the PAHs concentration on the solid matrix is linear up to CPAHs = 2 × 10 -8 g/l.…”
Section: Resultsmentioning
confidence: 99%